Dual-specificity tyrosine phosphorylation-regulated kinase 1A ameliorates insulin resistance in neurons by up-regulating IRS-1 expression - Tian, Shijiao (J Biol Chem, 2019)
Insulin resistance in the brain is a pathological mechanism that is shared between Alzheimer's disease (AD) and type 2 diabetes mellitus (T2DM). Although aberrant expression and phosphorylation of insulin receptor substrate 1 (IRS-1) contribute to insulin resistance, the underlying mechanism remains elusive. In this study, we used several approaches, including adeno-associated virus-based protein overexpression, immunoblotting, immunoprecipitation, immunohistochemistry, and in situ proximal ligation assays, to investigate the function of dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A) in IRS-1 regulation and the downstream insulin signaling in neurons. We found that DYRK1A overexpression up-regulated IRS-1 expression by slowing turnover of the IRS-1 protein. We further observed that DYRK1A directly interacted with IRS-1 and phosphorylated IRS-1's multiple serine residues. Of note, DYRK1A and IRS-1 were coordinately up-regulated in the prefrontal cortex of db/db mice brain. Furthermore, DYRK1A overexpression ameliorated chronic high insulin-induced insulin resistance in SH-SY5Y cells as well as in primary rat neurons. These findings suggest that DYRK1A protects against insulin resistance in the brain by elevating IRS-1 expression.